Studi Upah dan Beban Biaya Pekerja Konstruksi di Indonesia (Studi Kasus: Pekerja Konstruksi Gedung di Pulau Jawa) - Stevia Lukmanasari, Srie Heruyani; Soemardi, Biemo W (Department of Civil Engineering, Diponegoro University, 2016)
Labor wages have a large portion (approximately 30%) of construction contract value. Therefore, company should pay attention to labor wages. Unfortunately, existing data about construction labor wages in Indonesian are only showed as daily wages (for labor) and monthly wages (for employee/permanent staff), while there’s no information about their labor burden. Therefore, objectives of this study are to identify the component and structure of construction labor burden and wages in Indonesia and also to identify all factors related. Research method used int this study are empirical and inductive methods. After all data has been collected from field survey, description of the construction labor burden and wages model was compiled into its components. Moreover, comparison analysis used to identify factors related to construction labor burden and wages. Results of data processing and analysis shows that: 1) Construction labor burden in Indonesia for both employee/permanent staff and labor commonly consist of direct and indirect payment, and conditional and lumpsum payment, but there are different distributions between each kind of labor. 2) Construction labor burden and wages in Indonesia commonly depend on company profile, project profile, and labor profile.